Do out-of-pocket payments for care for children under 5 persist even in a context of free healthcare in Burkina Faso?: evidence from a cross-sectional population-based survey - Tapsoba, Ludovic D. G.; Yara, Mimbouré; Nakovics, Meike Irene; Somda, Serge M. A.; Lohmann, Julia; Robyn, Paul J.; Hamadou, Saidou; Hien, Hervé; De Allegri, Manuela (Healthcare, 2023)
Background: In April 2016, Burkina Faso began free healthcare for children aged from 0 to 5 years. However, its implementation faces challenges, and the goal of this study is to estimate the fees paid for this child care and to determine the causes of these direct payments. Methods: Data gathering involved 807 children aged from 0 to 5 years who had contact with the public healthcare system. The estimation of the determinants of out-of-pocket health payments involved the application of a two-part regression model. Results: About 31% of the children made out-of-pocket payments for healthcare (an average of 3407.77 CFA francs per case of illness). Of these, 96% paid for medicines and 24% paid for consultations. The first model showed that out-of-pocket payments were positively associated with hospitalization, urban area of residence, and severity of illness, were made in the East-Central and North-Central regions, and were negatively associated with the 7 to 23 month age range. The second model showed that hospitalization and severity of illness increased the amount of direct health payments. Conclusion: Children targeted by free healthcare still make out-of-pocket payments. The dysfunction of this policy needs to be studied to ensure adequate financial protection for children in Burkina Faso.
Gesehen am 05.07.2023